2008
DOI: 10.1111/j.1365-2710.2008.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of high-dose methotrexate in Japanese adult patients with malignancies: a concurrent analysis of the serum and urine concentration data

Abstract: The newly developed population pharmacokinetic model should improve the quality of serum concentration monitoring of high-dose MTX to predict and control toxic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 21 publications
12
46
0
Order By: Relevance
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
“…The former was the combination that had the weakest correlations in the present study, and the latter was the most frequently reported combination in previous studies. [9][10][11][12][13][14][15][16][17][18][19] As shown above, the sum of the absolute value of correlation coefficients among V 1 , k 10 , k 12 , and k 21 was 1.05 for regimen B, whereas V 1 , V 2 , CL, and Q was 3.29 for regimen B. Because of the relatively strong correlations among V 1 , V 2 , CL, and Q, this combination of the population parameters was considered to be a good target for a comparison with V 1 , k 10 , k 12 , and k 21 .…”
Section: Evaluation Of the Effect Of Correlations Among Population Pamentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that renal clearance is the principal pathway of MTX elimination and that the elimination of MTX appears to be related to kidney function [14][15][16]. Indeed, Skarby et al previously reported that the increase in serum creatinine (Cr) concentration within the first 12 to 24 hours after the start of MTX infusion was a good predictor of delayed elimination of MTX in Swedish children with ALL [14].…”
mentioning
confidence: 99%